Punishment and Welfare revisited - Garland, David (Punishment & society, 2019)
First published in 1985, Punishment and Welfare: A History of Penal Strategies develops a number of themes that continue to animate the research agenda of today’s sociology of punishment. This essay is a revised version of a new Preface written for the 2018 reprint edition of the book that reflects on its findings and method and their relevance in the current conjuncture.